Filsafat Pendidikan sebagai Konsep Pengembangan Kurikulum Pendidikan di SD 1 Panggarangan - Mutiara Citra Amalia; Desty Endrawati Subroto; Intan Nurmaliya; Risti Fauziah; Putri Robiatul Aliyah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study examines the role of philosophy in curriculum development at SD 1 Panggarangan. Philosophy of education, as a philosophical foundation, provides a strong framework for designing relevant and meaningful learning for students. This study aims to understand how the principles of educational philosophy, such as perennialism, essentialism, and progressivism, influence curriculum design at SD 1 Panggarangan. Using a descriptive qualitative method, this study gathers data via literature reviews and interviews to explain the research findings. The results show the philosophy of education plays an important role in determining the objectives, content, methods, and evaluation of the curriculum at SD 1 Panggarangan.